2021
DOI: 10.1021/acsearthspacechem.1c00331
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Large Bias in Rooftop Measurements of Atmospheric Ammonia

Abstract: In contrast to Europe and the U.S., human excreta in urban China are mainly stored in septic tanks beneath buildings, and the generated odors (including NH3) are released into the atmosphere through connecting pipes on the rooftops, that is, ceiling ducts. Here, we show that the levels of NH3 in ceiling ducts were 3 to 5 orders of magnitude higher than urban background concentrations. Unfortunately, urban air quality monitoring sites in China are mostly set on the roofs of various buildings. As the first attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Despite the dominant role of agricultural sources of NH 3 at global or regional scales, recent observations have revealed that NH 3 concentrations are higher in densely populated urban areas that have low agricultural activity. This finding posed a challenge to simulations driven by the current NH 3 emission inventories (EIs), as they could not accurately reproduce the observed high NH 3 concentrations in urban areas. Meanwhile, more and more isotopic source apportionment results pointed out that nonagricultural activities, such as fossil fuel combustion, industrial processes, on-road traffic, , slip from power plants, and waste, presented a larger contribution to atmospheric NH 3 concentration in urban areas as compared to the agricultural sectors. As shown in Table S1, during nonpollution periods, the contribution of nonagricultural sources to atmospheric NH 3 concentrations in the regions across China varied from 14 to 76%, and these values even reached 49–97% during haze periods. However, the relative contributions of nonagricultural and agricultural sources to the total NH 3 emissions from the isotopic source apportionment results significantly differed from those derived from the bottom-up anthropogenic NH 3 EIs (e.g., the Multi-resolution Emission Inventory for China, MEIC) at the city level (Figure S1). For instance, isotopic source apportionment revealed that fossil fuel was a significant source of NH 3 at an urban site in Beijing, contributing as much as 76%, whereas the corresponding value was only 35% based on the NH 3 EI .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the dominant role of agricultural sources of NH 3 at global or regional scales, recent observations have revealed that NH 3 concentrations are higher in densely populated urban areas that have low agricultural activity. This finding posed a challenge to simulations driven by the current NH 3 emission inventories (EIs), as they could not accurately reproduce the observed high NH 3 concentrations in urban areas. Meanwhile, more and more isotopic source apportionment results pointed out that nonagricultural activities, such as fossil fuel combustion, industrial processes, on-road traffic, , slip from power plants, and waste, presented a larger contribution to atmospheric NH 3 concentration in urban areas as compared to the agricultural sectors. As shown in Table S1, during nonpollution periods, the contribution of nonagricultural sources to atmospheric NH 3 concentrations in the regions across China varied from 14 to 76%, and these values even reached 49–97% during haze periods. However, the relative contributions of nonagricultural and agricultural sources to the total NH 3 emissions from the isotopic source apportionment results significantly differed from those derived from the bottom-up anthropogenic NH 3 EIs (e.g., the Multi-resolution Emission Inventory for China, MEIC) at the city level (Figure S1). For instance, isotopic source apportionment revealed that fossil fuel was a significant source of NH 3 at an urban site in Beijing, contributing as much as 76%, whereas the corresponding value was only 35% based on the NH 3 EI .…”
Section: Introductionmentioning
confidence: 99%